Criminal Responsibility of Money Laundering from The Proceeds of Narcotics Abuse in Bandar Lampung - Astri Ruli Yolanda; Assyifa, Frimadesta Nur (Jurnal Terekam Jejak, 2024)
Money laundering cases that originate from narcotics buying and selling transactions carry quite severe criminal sanctions, including being subject to corporal punishment and also being subject to fines . This research will use an approach juridical normative , implemented through study documents to conduct research and review sources of planned legal materials in the form of written regulations. Conclusions of Research is based on the reality obtained throughout hearing ongoing , the panel of judges did not get it information that can be liberating perpetrator from accountability legal action , either as justification and or reason forgiveness , therefore the panel of judges concluded that the action was carried out The suspect must be held accountable to him and because the perpetrator can be held responsible , then the defendant must be declared guilty of the case charged to him , and must be given a mandatory criminal sanction equal to his actions . Defendant criminal Money laundering is also responsible his active actions through the sale of narcotics are punishment criminal 9 years in prison as well penalty worth IDR 1,000,000.000,- (One billion rupiah) with conditions if the sanctions are not paid will replaced a sentence of 3 months in prison , decided several pieces of evidence were taken by the State and confiscated will crushed and burdened to pay court costs​ worth Rp. 2,000,- (two thousand rupiah).